Nanoparticle-Mediated Active Targeted Drug Delivery - Okhil K. Nag; Ryan N. Porell; James B. Delehanty (Pharmaceutical Research: Recent Advances and Trends Vol. 9, 2024)
Targeted and temporal delivery of drugs to diseased tissues is a key objective in medicine. Nanoparticles (NPs), as delivery vehicles, demonstrated the potential to achieve this by targeted delivery and controlled release of drugs while reducing off-target toxicity and minimizing the need for frequent dosing. Significant progress in NP-mediated drug delivery (NMDD) has focused on developing NP-based drug (NP-drug) formulations for targeted delivery to diseased tissues, with particular attention to cellular and subcellular precision. Advancements in this area include the intricate design of targeted NP-drug constructs to navigate through biological barriers, control drug release, overcome multidrug resistance (MDR), decrease side effects, and improve overall drug efficacy. This chapter outlines the latest developments in NP-mediated targeted drug delivery, highlighting various NP-drug constructs engineered to achieve active targeted delivery and improve therapeutic outcomes for critical diseases such as cancer, rheumatoid arthritis, and Alzheimer’s disease. The chapter concludes with an overview of current clinical trials in active targeted NP-drug delivery and discusses potential future directions for this rapidly evolving field.